Effectiveness of combination Integrated Dengue Education and Learning module (iDEAL) and Aedestech Mosquito Home System (AMHS) in dengue prevention among school children in Selangor and Kuala Lumpur: study protocol for a randomised controlled trial - Dapari, Rahmat; Jumidey, Abdul Qayyum; Hwa, Lim Chee; Muniandy, Kalaivani; Bakar, Suhaili Abu; Mohd Desa, Mohd Nasir; Sandhu, Sukhvinder Singh; Mustapha, Nooreen Farzana; Ahmad Zamzuri, Mohd Ammar Ihsan; Hassan, Mohd Rohaizat; Che Dom, Nazri; Syed Abdul Rahim, Syed Sharizman; et al. (Universiti Putra Malaysia Press, 2024)
Introduction: Dengue is a viral disease that is transmitted by mosquitoes and highly prevalent in Malaysia. The disease is caused by fourdistinct subtypes of dengue virus (DENV) that are closely related. In Malaysia, a total of 123,133 dengue cases were reported in 2023, com-pared to 7,103 cases reported in 2000. Selangor and Kuala Lumpur recorded the highest number and incidence rate of dengue cases and re-lated mortality. Methods: This article presents a protocol to explore the efficacy of a combined intervention, integrated dengue education andlearning module (iDEAL) and Aedestech Mosquito Home System (AMHS), in improving schoolchildren’s knowledge, attitude, practice (KAP),including environmental cleanliness index and dengue index in Selangor and Kuala Lumpur. Primary (n = 10) and secondary schools (n = 10)in the study locations will be recruited for the cluster randomised controlled trial (RCT) for a 2-year period. The intervention group will be sub-jected to a combined theory-based intervention, IDEAL and AMHS, while the control group will receive conventional education. The efficacyof the intervention module will be evaluated at four time points. Data will be analysed using the Generalised Linear Mixed Model (GLMM) forthe main and interaction effectsat each follow-up point. P-values of 0.05 and 95% confidence interval will be considered for hypothesis testing. Discussion: The findings from this study will assist in identifying effective educational strategies for enhancing KAP among this vulnera-ble young population in Selangor and Kuala Lumpur, and possibly other states in Malaysia. Trial Registration: This trial has received ap-proval from the Ethics Committee for Research Involving Human Subjects of Universiti Putra Malaysia (JKEUPM-2023-635) and the NationalMedical Research Registration of Malaysia (NMRR) (NMRR ID-23-02822-CPZ). Additionally, the RCT has been registered with the Thai Clini-cal Trial Registry (TCTR) (Reference number: TCTR20230513002).